EFFECTS OF ELECTROACUPUNCTURE, ACUPRESSURE MASSAGE, AND HERBAL FOOT SOAKING IN THE TREATMENT OF SCIATICA CAUSED BY SPINAL DEGENERATION (Vietnam Journal of Community Medicine, 2026)
Background: Sciatica due to lumbar spine degeneration is a common condition that causes persistent pain and limits mobility. Combining multiple traditional medicine therapies may improve treatment outcomes.Objective: To evaluate the effectiveness of electroacupuncture, acupressure massage, and herbal foot soaking using the “NK formula” in treating sciatica caused by spinal degeneration.Methods: A before–after clinical intervention study was conducted on 50 patients with sciatica due to spinal degeneration. Patients received a 21-day treatment regimen including herbal foot soaking (“NK formula”), acupressure massage, and electroacupuncture at Bao Yen Regional General Hospital from April to October 2025.Results: After 21 days, patients showed significant improvements in pain intensity (VAS score), lumbar spine flexibility (Schober test), nerve root compression signs (Lasegue test and Valleix points), and daily functional ability (ODI index) (p < 0.05). No adverse effects were reported.Conclusion: The combination of herbal foot soaking (“NK formula”), acupressure massage, and electroacupuncture is a safe and effective treatment for sciatica caused by spinal degeneration.
Keywords: Electroacupuncture, acupressure massage, foot soaking, sciatica, spinal degeneration.